THE PROLIFERATIVE AND ANAMNESTIC ANTIBODY RESPONSE OF RABBIT LYMPHOID CELLS IN VITRO : I. IMMUNOLOGICAL MEMORY IN THE LYMPH NODES DRAINING AND CONTRALATERAL TO THE SITE OF A PRIMARY ANTIGEN INJECTION - Jacobson, E. B. (The Rockefeller University Press, 1969)
Popliteal lymph nodes were obtained from rabbits 4 days to 9 months after a primary injection of diphtheria toxoid or bovine γ-globulin into the footpad. The ability of cells from these nodes to proliferate upon reexposure to antigen in vitro was compared to the height of the secondary response produced by tissue fragments. In addition, a comparison was made between the responsiveness of draining and contralateral lymph nodes. While the secondary antibody response in vitro increased markedly with the time after immunization at which the lymph nodes were taken from the animals, the degree of proliferation induced by antigen was highest with cells from lymph nodes taken early after priming (peak day 7) and was very much lower with lymph node cells taken longer than 3 wk after priming. This striking difference between these two responses has been discussed. Contralateral lymph nodes were much inferior to draining nodes in their ability to give a secondary antibody response in vitro, and never gave a detectable proliferative response. This difference became less marked with time after priming, but could still be demonstrated after 4 months. These results suggest a concentration of primed cells in the lymphoid tissue draining the site of injection, and a slow release of these cells into the circulation, to be distributed to the remaining lymphoid tissue.